(untitled) (Journal of Mathematical Study, 2021)
Let I be an ideal of a ring R. We call R weakly I-semiregular if R/I is a von Neumann regular ring. This definition generalizes I-semiregular rings. We give a series of characterizations and properties of this class of rings. Moreover, we also give some properties of I-semiregular rings.